2005
DOI: 10.1007/s10571-005-8469-y
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic Acid Inhibits the Release of the Neurotrophic Fibroblast Growth Factor (FGF)-1 and Enhances Proliferation of Glia Cells, in vitro

Abstract: 1. Kynurenic (KYNA) and quinolinic (QUIN) acids are neuroactive tryptophan metabolites formed along the kynurenine pathway: the first is considered a non-competitive antagonist and the second an agonist of glutamate receptors of NMDA type. The affinity of these compounds for glutamate receptors is, however, relatively low and does not explain KYNA neuroprotective actions in models of post-ischemic brain damage. 2. We evaluated KYNA effects on the release of fibroblast growth factor (FGF)-1, a potent neurotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…A similar effect was previously reported in synoviocytes [16]. In contrast, Di Serio et al [1] reported the stimulatory effect of KYNA on the proliferation rate of mouse microglia and human glioblastoma cells in vitro. Although we investigated the effect of KYNA in a broad range of concentrations from 0.00001 to 10 mM, we did not observe the stimulatory activity of KYNA in HT-29 cells.…”
Section: Resultssupporting
confidence: 82%
“…A similar effect was previously reported in synoviocytes [16]. In contrast, Di Serio et al [1] reported the stimulatory effect of KYNA on the proliferation rate of mouse microglia and human glioblastoma cells in vitro. Although we investigated the effect of KYNA in a broad range of concentrations from 0.00001 to 10 mM, we did not observe the stimulatory activity of KYNA in HT-29 cells.…”
Section: Resultssupporting
confidence: 82%
“…It has been shown that QUIN can directly increase proliferation rate of human glioblastoma cell line U343MG (Serio et al, 2005), and we showed here that QUIN can increase SK-N-SH neuroblastoma cell proliferation. Interestingly, QUIN also increases astroglial production of glial cell line-derived neurotrophic factor (Bresjanac and Antauer, 2000), which may induce proliferation of neuroblastoma cells and increase resistance to chemotherapeutic agents (Hansford and Marshall, 2005) (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…NGF is of special importance because of its regulation of proliferation and subsequent maintenance of cholinergic neurones in the CNS, and hence of relevance to AD and schizophrenia [52]. In contrast, kynurenic acid reduced the release of fibroblast growth factor-1 (FGF-1) in several different experimental models [53], so that its net effects on cell viability may depend on a balance of changes in different growth factors.…”
Section: Growth Factorsmentioning
confidence: 99%